A Feasibility study on a Solid Waste Management System for the Municipality of Cainta - Dela Paz, Rupher (College of Engineering, 2001)
The municipality of Cainta has no formal and official waste management system to handle its solid wastes. Because of this, the residents and owners of some establishments resort to either burning their trash or dumping them on the sidewalks. In this light, the group has devised a system dedicated to the solid waste management in the municipality of Cainta. The Solid Waste Management will offer collection services, waste segregation services and disposal services for the residents and establishments in Cainta. These services allow Waste Management to offer a full range of environmental services to approximately 45,798 households, plus several commercial establishments and institutions. Waste management tailors its services to each resident of Cainta and to establishments to ensure timely and effective response to customer needs. It is strongly committed to the safe and responsible disposal of waste, working diligently to ensure regulatory compliance and protection of the public's health and natural resources. A demand analysis was conducted using the linear regression method in order to project the demand (volume of solid waste) for the next five years. Domestic or household wastes comprise the majority (68%) of the total volume generated within the municipality. Thus, it is reasonable to focus most of the attention and resources on this sector. More of the information-dissemination efforts, transportation prioritization, activity monitoring, etc. will go to the households. A marketing plan that has strategies for the service, pricing, promotions, and place (distribution) was formulated. This project is non-commercial by nature. It is being developed for the purpose of creating a system for a local government unit. This is a government-aided project, and since there are no private sectors handling waste management in Cainta, there are no competitors considered. The flow of the process will start from the individual households and commercial establishments, from where the solid waste will originate. Trash will be collected twice a week. The specific days and which barangays will be serviced together are based on the size and location of the barangays. Garbage pick up points will be street comers in order to eliminate the need for the garbage trucks to enter each and every side street. This will be turned over to the local government unit (LGU), which will then be in charge of dumping the non-recyclable waste on a landfill and selling the recyclable ones to the recycling facilities and junk shops. For the collection services to be effective the measures such as point of collection, frequency of refuse collection and type of equipment to be used are evaluated by the group. Potential suppliers will be the pre-qualified private contractors that were initially screened for public bidding by the MMDA based on certain criteria. The LGU provided a land that is suitable for a landfill, as it is far from residential areas and any body of water. Within the premises of the landfill site is a segregation facility. The nonrecyclable, or biodegradable, waste will be dumped into the landfill, while the recyclables, or nonbiodegradable materials, will be sold to recycling facilities. The project is also economically feasible, for it will provide net positive gains to both the environment and the society. After the evaluation of the results of the financial projections and tests of profitability, the project was proven to be financially viable. Overall, this project of having a solid waste management system for the municipality of Cainta was proven to be feasible technically, financially, socially, and on a marketing level.